THE GENESIS OF LEGAL REGULATION OF ENVIROMENTALLY HAZAARDOUS ACTIVITY IN THE FIELD OF AVIATION BE THE LEGISLATION OF UKRAINE (FROM ANCIENT TIMES TO THE PERIOD OF INDEPENDENCE) - Краснова, Ю. А. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2008)
The article deals with the genesis of legal regulation of environmentally hazardous activity in the field of aviation legislation of Ukraine.